Política externa chilena e espectro ideológico político-partidário: um estudo sobre a Câmara dos Deputados (2002-2006) - Pedro Feliú Ribeiro; Amâncio Jorge Silva Nunes Oliveira; Manoel Galdino (Universidade do Estado do Rio de Janeiro, 2009)
The influence of political parties on decisions made by members of Congress is a hotly debated issue in political science. In foreign policy, which is usually considered nonpartisan, the matter is even more inconclusive. The current study analyzes all the roll-call votes taken on foreign policy issues in the 2002-2006 legislature of the Chilean Chamber of Deputies. After tracing a spatial map of foreign policy preferences among Chilean Deputies using the Nominate statistical package, we concluded that the ideology of the legislator's political party is a predictive factor for his or her foreign policy behavior. Our findings indicate that the way Chilean legislators structure their preferences on foreign policy issues does not differ significantly from the way they shape their domestic policy preferences.